The Influence of the “Non-Aggression Pact” of 1932 on the Development of Trade Relations between the USSR and Poland (Global Journal of Human-Social Science, 2024)
The article examines the state of Soviet-Polish trade relations based on of periodic materials from the end of July 1932 to the middle of November 1933 It is proved that the planned preparation for the conclusion of the Non- Aggression Treaty with Poland was also on the agenda and on the problem of improving Soviet-Polish trade relations extension of the agreement on Soviet-polish trade February 17 1933 normalization of the issue of railway tariffed signing of the convention on the rafting of timber along border rivers June 19 1933 and the agreement on the export of wood
Keywords: riga peace treaty; soviet-polish trade; nonaggression pact; periodicals